Use of fermentation with animal and vegetable materials as silk wood media materials (Tubifex sp) - Umidayati Umidayati (Departemen Akuakultur FPIK UNDIP, 2021)
AbstractSilk worms are the initial feed larvae that have high protein content and have a size in accordance with the opening of the larva's mouth. This study aimed to determine the best fermented media with animal and vegetable ingredients with different dosage differences for the cultivation of silk worm as substitute for chicken manure. This study used a completely randomized design (CRD) with 5 treatments in triplicates: Treatment A (100% fish silage + 10 ml molasses + 1 ml probiotics + 100 ml water), Treatment B (75% fish silage + 25% vegetable waste + molasses 10 ml + 1 ml probiotics + 100 ml water), Treatment C (50% fish silage + 15% vegetable waste + 10% bran + 25% tofu waste + 10 ml molasses + 1 ml probiotics + 100 ml water), Treatment D ( 25% fish silage + 25% vegetable waste + 10% bran + 40% tofu waste + 10 ml molasses + 1 ml probiotics + 100 ml water), and Treatment E (100% vegetable waste + 1 ml probiotics + 10 ml molasses + 100 ml water ). Research results showed the highest growth was obtained by Treatment D with an average absolute biomass of 39,496 ± 1,080 g/container while the productivity value was 454.14 ± 9,001 g/m2/cycle. The ANOVA test with reliance of 95% showed that the average growth of the four treatments are significantly different.